Judicial recognition of living customary law in the context of women's matrimonial property rights in South-East Nigeria - Diala, Anthony Chima (Department of Private Law, 2025)
The interaction of customary law with state law raises challenges for policy-makers in postcolonial societies. This study contends that these challenges are primarily caused by state recognition of customary law without proper attention to how people adapt it to modern conditions vastly different from its agrarian origins. Recognition denotes the manner customary law norms and institutions are 'incorporated into the state legal system' or enforced by state organs such as courts. It often raises the question of which version of customary law is recognised. Scholars have identified two broad types - official customary law and living customary law. Generally, they define living customary law as the norms that regulate people's daily lives, while official customary law represents the version perceived by state officials typically as legal rules, and often recorded in codes, legislation, and law reports. Drawing from the semi-autonomous social field theory, this study conceptualises living customary law as the law that emerges from people's adaptation of customs to socio-economic changes. It argues that because it emerges in this manner, its judicial recognition is inhibited by a rule-based approach to adjudication. The study utilises literature review, interviews, archival searches, and case analysis to investigate the ways in which judges acknowledge living customary law in the context of women's matrimonial property rights in South-East Nigeria. It finds that while women are generally apathetic to matrimonial property claims, judges are generally insensitive to customary law's process-oriented character and pay scant attention to how customs are being adapted to socio-economic changes. It further finds that judicial recognition of living customary law is hampered by a colonial legacy of rule-based adjudication, disregard for the values that inform customary law, and judges' non-resort to constitutional values that could promote women's matrimonial property rights. Connected to this finding is the failure of the Constitution to provide for these rights and define customary law's status in the legal system. The study concludes that judicial recognition of living customary law is inhibited by Nigeria's poor legal framework and the technical nature of court rules. It suggests that the manner people adapt customs to socio-economic changes should guide judicial and legislative approaches to customary law